2020
DOI: 10.3389/fonc.2020.01777
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of COVID-19 in Patients With Lung Cancer Treated in a Tertiary Hospital in Madrid

Abstract: Background: Cancer patients represent a vulnerable population for COVID-19 illness. We aimed to analyze outcomes of lung cancer patients affected by COVID-19 in a tertiary hospital of a high-incidence region during the pandemic. Methods: We annotated 23 lung cancer patients consecutively diagnosed with COVID-19 at our institution (HGUGM; Madrid, Spain) between March 4th, 2020 and May 12th, 2020. Only patients with a confirmatory SARS-CoV-2 RT-PCR were included in the study. Results: All patients had at least 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 34 publications
0
38
0
Order By: Relevance
“… Sha et al 78 The impact of the COVID-19 pandemic on lung cancer patients China Retrospective cohort study 161 patients Secondary care • Response evaluation criteria in solid tumour (RECIST 1) • Delayed admission 29.4% ( n = 47) patients had delayed admission during the epidemic and having to discontinue or delay their regular anticancer treatments. Of these 47 delayed patients, 33 were evaluated for tumour status using a computed tomography scan, 6 of these 33 cases (18.2%) were diagnosed as progressive disease (PD) and 5 cases did not return for visit Calles et al 79 Outcomes of COVID-19 in patients with lung cancer treated in a tertiary hospital in Madrid Spain Observational, retrospective cohort single-centre study 23 patients Secondary care • Clinical features, • Pathology, laboratory and Radiological data • Treatment schemes All patients had at least 1 COVID-19-related symptom; cough (48%), shortness of breath (48%), fever (39%) and low-grade fever (30%) were the most common. Time from symptoms onset to first positive SARS-CoV-2 PCR was 5.5 days (range 1–17), with 13% of cases needed from a second PCR to confirm diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“… Sha et al 78 The impact of the COVID-19 pandemic on lung cancer patients China Retrospective cohort study 161 patients Secondary care • Response evaluation criteria in solid tumour (RECIST 1) • Delayed admission 29.4% ( n = 47) patients had delayed admission during the epidemic and having to discontinue or delay their regular anticancer treatments. Of these 47 delayed patients, 33 were evaluated for tumour status using a computed tomography scan, 6 of these 33 cases (18.2%) were diagnosed as progressive disease (PD) and 5 cases did not return for visit Calles et al 79 Outcomes of COVID-19 in patients with lung cancer treated in a tertiary hospital in Madrid Spain Observational, retrospective cohort single-centre study 23 patients Secondary care • Clinical features, • Pathology, laboratory and Radiological data • Treatment schemes All patients had at least 1 COVID-19-related symptom; cough (48%), shortness of breath (48%), fever (39%) and low-grade fever (30%) were the most common. Time from symptoms onset to first positive SARS-CoV-2 PCR was 5.5 days (range 1–17), with 13% of cases needed from a second PCR to confirm diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…As COVID-19 is a disease of the respiratory tract, previous studies have concluded that patients with lung cancer often experience severe manifestations when infected by SARS-CoV-2 and are at a higher mortality risk than patients with other cancer types ( Antonio et al, 2020 ). An investigation that took place in China suggested that 18 out of 1590 cases of COVID-19 patients had a cancer history.…”
Section: Introductionmentioning
confidence: 99%
“…According to the scales mentioned above, all included studies were of high quality, with no less than five points. For the above 13 studies, 10 studies ( [1] , [2] , [3] , [7] , [8] , [9] , [10] , [11] , [12] , [13] ) reported the number of deaths in patients with lung cancer and other tumors, whereas the other 3(4-6) studies only reported on lung cancer populations and could not provide OR. Therefore, we included the first 10 studies in the meta-analysis and discussed all 13 studies in the systematic review for more information on the outcomes.…”
Section: Resultsmentioning
confidence: 99%